Higher Integrability for Very Weak Solutions of Inhomogeneous A-Harmonic Form Equations - Yuxia Tong; Shenzhou Zheng; Jiantao Gu (Journal of Applied Mathematics)
The higher integrability for very weak solutions of A-harmonic form equations d*A(x,u,du)=B(x,u,du) has been proved.